2006
DOI: 10.1177/1359105306058852
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Patient Perceptions of the Physician Explanations in Medical Encounters

Abstract: Although, in actual practice, physicians have to subjectively judge the level of the explanation that they provide, little is known about this judgment. Therefore, making use of 630 physician-patient pairs in Japan, we investigated the association between patient and physician evaluations of physician explanations of medical test results and diagnoses. We found that the physician's judgment does not always agree with that of the patient, with regard to the level of explanation necessary. In addition, we first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Previous studies 25 have demonstrated that when HCPs received information about headache-related impairment in addition to symptoms, frequency, and pain intensity, their appreciation of the severity of the patient's migraines increased, as did the likelihood that they would prescribe migraine-specific medication with more aggressive follow-up. While the degree of misalignment found in this study may seem high, similar findings have been seen in other therapeutic areas [45][46][47] suggesting that narrowly focused questions …”
Section: Discussionsupporting
confidence: 88%
“…Previous studies 25 have demonstrated that when HCPs received information about headache-related impairment in addition to symptoms, frequency, and pain intensity, their appreciation of the severity of the patient's migraines increased, as did the likelihood that they would prescribe migraine-specific medication with more aggressive follow-up. While the degree of misalignment found in this study may seem high, similar findings have been seen in other therapeutic areas [45][46][47] suggesting that narrowly focused questions …”
Section: Discussionsupporting
confidence: 88%
“…Hagihara proposed a method for the objective evaluation of physician-patient communications (Hagihara et al 2005(Hagihara et al , 2006a(Hagihara et al , 2006b) that avoids the above-mentioned problems of RIAS and also takes into consideration the observation that the patient's subjective evaluation of the conversation during a consultation, and that of the physician's explanation, have stronger effects than the amount of objective explanation offered in determining subsequent patient behavior (Northouse and Northouse 1992). In concrete terms, this method evaluates a physician-patient pair using questionnaire forms containing identical questions regarding physician-patient communication, and assesses the discordance between the physician's and the patient's perceptions regarding the extent of the physician's explanation ( Figure 1).…”
Section: A Commonly Used Methods For Quantitative Evaluation Of Physicmentioning
confidence: 99%
“…When the practitioner score is equal to the patient score ("Concordance"), the interaction is considered a good one (Figure 1). A survey that examined pairs of physicians in Fukuoka Prefecture and their patients (Hagihara et al 2005(Hagihara et al , 2006a(Hagihara et al , 2006b showed Acupuncture practitioner-patient communication that "Discordance, Physician Better" was associated with a signifi cantly lower patient satisfaction regarding therapy than "Concordance" or "Discordance, Patient Better," and that a significantly larger proportion of patients visited multiple medical institutions for the same medical problem. Based on these results, they claimed that the dichotomy into "Discordance, Physician Better" and other cases ("Concordance" or "Discordance, Patient Better") was a useful method for evaluating professional-patient communication.…”
Section: A Commonly Used Methods For Quantitative Evaluation Of Physicmentioning
confidence: 99%
“…Além disto, não houve correlação entre as percepções destes indivíduos quanto às explicações referentes ao tratamentopor exemplo, efeitos do tratamento, efeitos colaterais, riscos, tratamentos alternativos. (HAGIHARA et al, 2006 Os profissionais tendem a usar a terminologia técnica porque ela é precisa e familiar. Além disto, nem sempre existe uma palavra não técnica que seja equivalente (HOUTS et al, 2006).…”
Section: Amplificação Sonora Individualunclassified